Long COVID and Aviation Safety - Young Hwan Kwon (Hanggong uju uihakoeji, 2022)
Since its emergence in Wuhan, China, COVID-19 has spread and had a profound effect on the lives and health of people around the globe. Most people who develop COVID-19 fully recover, but current evidence suggests approximately 10% to 20% of people experience a variety of mid- and long-term effects after they recover from their initial illness. These mid- and long-term effects are collectively known as post covid-19 condition or “long COVID”. Studies have shown that a significant number of patients complain of multiple symptoms over a period of several months or longer. The symptoms of long covid include fatigue or muscle weakness, dyspnea, cognitive impairment, and depression or anxiety. These chronic symptoms can also negatively affect aviation safety. Therefore, this review summarizes studies of the long-term effects of COVID-19, and aeromedical implications of long COVID.